2022
DOI: 10.3390/diagnostics12061451
|View full text |Cite
|
Sign up to set email alerts
|

The Non-Invasive Ultrasound-Based Assessment of Liver Viscosity in a Healthy Cohort

Abstract: Liver fibrosis is the most significant prognostic factor in chronic liver disease (CLD). Clinical practice guidelines recommend the use of non-invasive techniques, such as two-dimensional shear-wave elastography (2D-SWE), to assess liver stiffness as a marker of fibrosis. Several other factors influence liver stiffness in addition to liver fibrosis. It is presumed that changes due to necro-inflammation modify the propagation of shear waves (dispersion). Therefore, new imaging techniques that investigate the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Our research found a link between Vi PLUS, which decreases with age, and with the measurement depth and BMI. Only a few studies that evaluated the liver used this non-invasive method to measure the viscosity of tissue [ 24 ], with Deffieux et al (2015) [ 44 ] being the first. We could indeed theorize that viscosity metrics that illustrate inflammatory states could be beneficial when assessing patients who have suffered acute kidney injury or acute pyelonephritis or when assessing kidney transplant recipients to evaluate acute rejections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research found a link between Vi PLUS, which decreases with age, and with the measurement depth and BMI. Only a few studies that evaluated the liver used this non-invasive method to measure the viscosity of tissue [ 24 ], with Deffieux et al (2015) [ 44 ] being the first. We could indeed theorize that viscosity metrics that illustrate inflammatory states could be beneficial when assessing patients who have suffered acute kidney injury or acute pyelonephritis or when assessing kidney transplant recipients to evaluate acute rejections.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of rapid deformation, slow deformation causes tissues to migrate, and necro-inflammation-related alterations are thought to affect how shear waves propagate (viscosity) [ 18 ]. Supersonic Imagine created the original 2D-SWE method, and numerous studies and meta-analyses have supported its usefulness in fibrosis assessment [ 19 , 20 , 21 , 22 ], but, currently, there are only a few research articles employing the new 2D-SWE PLUS and Vi PLUS technologies [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their results show that viscosity was only a weak predictor of disease activity and steatosis levels and that it had a poorer predictive value for fibrosis, compared to stiffness. Normal liver viscosity values on the same device, using the same technique, were found by our group to be around 1.59 Pa·s [ 29 ]. In contrast with our findings, liver values of ViPLUS did increase with age but the concept of “inflammaging” described for the liver—the increase in necroptosis associated with age—is not characteristic for thyroid tissue [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 92%
“…In another study utilizing Vi.Plus by SSI, the mean viscosity of 131 healthy adults was 1.59 Pa·s. After multivariate analysis, age and body mass index (BMI) were significantly associated with Vi.Plus [ 52 ]. In contrast, Trout et al found no significant correlation between SWDS and BMI, but a significant positive correlation between SWDS and abdominal wall thickness and median measurement depth [ 50 ].…”
Section: Clinical Studiesmentioning
confidence: 99%